Cisco CCNP ENCOR v1.1 (350-401) Cert Prep: 1 Architecture, Virtualization, and Infrastructure. - Wallace, Kevin (linkedin.com, 2023)
Prepare for the first three domains of the Cisco CCNP ENCOR (350-401) certification exam: Architecture, Virtualization, and Infrastructure.